Harley Quinn & the Gotham City Sirens - Dini, Paul (DC Comics, 2024)
"Catwoman, Poison Ivy and Harley Quinn are tired of playing by other peoples' rules regardless of which side of the law they're on. They have a new agenda that's all their own, and they'll use any means necessary to pursue it. But can they get along and work as a team? And who will get hurt along the way?"--